Journalism and PR: News, Media and Public Relations in the Digital Age - Lloyd, J; Toogood, L (I.B.Tauris, 2014)
Public relations and journalism have had a difficult relationship for over a century, characterised by mutual dependence and – often – mutual distrust. In recent years, developments in corporate PR and in political communications mean that the news media outlets are less and less important to the persuaders. The communications business is often able to bypass the gatekeepers. The internet, especially social media, has made reputation more precarious – but it has also given companies, governments and public figures channels of communication of their own. The need to proclaim and protect the brand – personal, corporate or political – means that public relations is now a top-table profession…whilst journalism struggles for survival. This unique study illuminates and analyses a new media age.